1970
DOI: 10.1002/mana.19700460105
|View full text |Cite
|
Sign up to set email alerts
|

Completions of BOOLEAN Algebras with operators

Abstract: The notion of a BooLEan algebra with operators was introduced by J~NSSON and TARSKI [ 5 ] . It encompasses as special cases relation algebras (TARSKI [9]), closure algebras (MCKINSEY-TARSKI [S]), cylindric algebras (HENRIN-TARSKI [4]), polyadic algebras (HALMOS [Z]), and other algebras which have been studied in recent years. One of the basic results of [5]is that any Booman algebra with operators can be extended to one that is complete and atomic. The extension does not preserve any Booman sums (joins) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 6 publications
0
45
0
Order By: Relevance
“…Our development parallels that of Jónsson [1994]; we also need some lemmas from Monk [1970] concerning complete extensions of operators. Jónsson's approach can actually be given an axiomatic formulation so that it applies not only to canonical extensions and completions, but possibly also to other kinds of extensions that have not yet been considered.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our development parallels that of Jónsson [1994]; we also need some lemmas from Monk [1970] concerning complete extensions of operators. Jónsson's approach can actually be given an axiomatic formulation so that it applies not only to canonical extensions and completions, but possibly also to other kinds of extensions that have not yet been considered.…”
mentioning
confidence: 99%
“…Monk [1970] extended the notion of the completion of a Boolean algebra to Boolean algebras with operators. Under the assumption that the operators of such an algebra A are completely additive, he showed that the completion of A always exists and is unique up to isomorphisms over A.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But a completion of a distributive lattice may not be a distributive lattice (e.g., [1]). In [13] Monk extended the definition of a completion to BAOs. Nowadays this construction is called the Dedekind-MacNeille completion, MacNeille completion or Monk completion.…”
Section: Introductionmentioning
confidence: 99%
“…Monk [13] proved that every positive equation is preserved under completions. Givant and Venema [8] extended this result by showing that all Sahlqvist equations are preserved under completions of conjugated BAOs (see also [18]).…”
Section: Introductionmentioning
confidence: 99%